STRATEGI PEMBELAJARAN BERDIFERENSIASI PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Farah Hilmy Dwijayanti (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2025)
This study aims to describe the planning, implementation, and evaluation strategies in differentiated learning in science learning at SD UMP. This research was conducted in the even semester of the 2023/2024 school year. Qualitative phenomenology is the type of approach chosen in this study. This study uses interview, observation, and documentation guidelines. The data analysis technique used in this study consists of three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study found things, namely the differentiated learning strategy in science learning has been carried out in essence, both from the planning, implementation, and evaluation strategies. The results of the study also show that there is an important role for the principal and teachers in ensuring that this differentiated learning strategy can run well and continue to be improved. Researchers can conclude from this study that the differentiated learning strategy in science learning starts from the planning stage by mapping student learning needs through diagnostic assessments which are used as the basis for teachers to design learning that is poured into the form of teaching modules. Furthermore, teachers in the implementation strategy include differentiation of content, process, product and learning environment. Differentiation here does not mean that teachers differentiate the entire learning for each student, but differentiation here means that teachers are able to create learning plans that accommodate students' learning needs and students feel comfortable in learning. The evaluation strategy for differentiated learning uses LKPD and test questions. Feedback is also provided to be used as reflection and evaluation material for teachers to design further learning.